Predictors and outcomes of obstructive sleep apnea in patients with chronic obstructive pulmonary disease in China - Zhang, Pan; Chen, Bi; Lou, Heqing; Zhu, Yanan; Chen, Peipei; Dong, Zongmei; Zhu, Xuan; Li, Ting; Lou, Peian (BMC pulmonary medicine, 2022)
"Overlap syndrome" refers to obstructive sleep apnea (OSA) combined with chronic obstructive pulmonary disease (COPD), and has poorer outcomes than either condition alone. We aimed to evaluate the prevalence and possible predictors of overlap syndrome and its association with clinical outcomes in patients with COPD. We assessed the modified Medical Research Council dyspnea scale (mMRC), Epworth sleepiness scale (ESS), COPD assessment test (CAT), Hospital Anxiety and Depression Scale (HADS), Charlson Comorbidity Index (CCI), and STOP-Bang questionnaire (SBQ) and performed spirometry and full overnight polysomnography in all patients. An apnea-hypopnea index (AHI) ≥ 5 events per hour was considered to indicate OSA. Risk factors for OSA in COPD patients were identified by univariate and multivariate logistic regression analyses. A total of 556 patients (66%) had an AHI ≥ 5 events per hour. There were no significant differences in age, sex ratio, mMRC score, smoking index, number of acute exacerbations and hospitalizations in the last year, and prevalence of cor pulmonale between the two groups (all p > 0.05). Body mass index (BMI), neck circumference, CAT score, CCI, ESS, HADS, and SBQ scores, forced expiratory volume (FEV) , FEV % pred, FEV /forced vital capacity ratio, and prevalence of hypertension, coronary heart disease, and diabetes were all significantly higher and the prevalence of severe COPD was significantly lower in the COPD-OSA group compared with the COPD group (p < 0.05). BMI, neck circumference, ESS, CAT, CCI, HADS, hypertension, and diabetes were independent risk factors for OSA in COPD patients (p < 0.05). SBQ could be used for OSA screening in patients with COPD. Patients with severe COPD had a lower risk of OSA compared with patients with mild or moderate COPD (β =  - 0.459, odds ratio = 0.632, 95% confidence interval 0.401-0.997, p = 0.048). Patients with overlap syndrome had a poorer quality of life, more daytime sleepiness, and a higher prevalence of hypertension and diabetes than patients with COPD alone. BMI, neck circumference, ESS, CAT, CCI, HADS, hypertension, and diabetes were independent risk factors for OSA in patients with COPD. The risk of OSA was lower in patients with severe, compared with mild or moderate COPD.